2021
DOI: 10.31101/ijhst.v2i2.1850
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Maternal Fetal Attachment

Abstract: Maternal Fetal Attachment and fetal growth are strongly influenced by the emotional state or anxiety of the mother, this can be seen from the psychological condition of the mother before giving birth.  The psychological condition of the mother will have an impact on the health and development of the fetus. In Indonesia, there are about 28.7% of pregnant women who experience anxiety in the third trimester. The research objective was to determine the relationship between anxiety and maternal fetal attachment. Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In Indonesia, there are about 28.7% of pregnant women experience anxiety in the third trimester. There is a relationship between stress and the attachment of pregnant women to the fetus (Wahyuntari & Puspitasari, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In Indonesia, there are about 28.7% of pregnant women experience anxiety in the third trimester. There is a relationship between stress and the attachment of pregnant women to the fetus (Wahyuntari & Puspitasari, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was found that the levels of worry about pain and distress likely to be experienced during labor affected the participants’ prenatal attachment levels. In studies in Turkey and the rest of the world, it has been discovered that pregnant women who had high levels of anxiety also had a lower quality of prenatal attachment (Coşkun et al, 2019; Pisoni et al, 2014; Wahyuntari & Puspitasari, 2021). Besides, Wilson and Simpson (2016) reported a positive relationship between anxiety about attachment and pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal attachment is the emotional relationship between the mother and the fetus during pregnancy. Maternal-fetal attachment plays a key role in the health of the mother and the fetus and has a significant effect on the mother’s decision to have a healthy lifestyle during her pregnancy (Wahyuntari & Puspitasari, 2021). To satisfy the needs of the fetus growing during pregnancy, certain physiological and psychological changes come into play (Soma-Pillay et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wahyuntari and Puspitasari investigated the relationship between pregnant women's anxiety and their attachment to the unborn baby in Indonesia using Zung self-rating anxiety to measure the PRA and the same tools as used in this study to measure MFA. They found a significant relationship between anxiety and MFA [32]. Another study found that maternal age has contributed to the MFA during pregnancy [27].…”
Section: Discussionmentioning
confidence: 99%